The Strategic Role of Micro, Small, and Medium Enterprises in Poverty Reduction among Rural Communities - Sitti Hasbiah (PT. Maju Malaqbi Makkarana, 2026)
The problem of poverty is still the main challenge for development in rural areas of Indonesia. Limited employment opportunities and low access to productive economic activities cause some village communities to be economically vulnerable. One of the sectors that is considered to have great potential in reducing poverty levels is Micro, Small, and Medium Enterprises (MSMEs). This article aims to conceptually examine the role of MSMEs in efforts to reduce poverty in rural communities by taking the context of Bantaeng Regency. The writing method uses a qualitative-descriptive approach through literature studies of scientific journals, reference books, and relevant official government documents published in the last five years. The results of the study show that MSMEs play a role as a driver of the local economy through the creation of job opportunities, increasing household income, and strengthening the economic independence of communities based on local potential. However, the development of MSMEs in rural areas is still faced with various structural obstacles, such as limited capital, low managerial capacity of business actors, and limited market access. Therefore, policy support and cross-stakeholder synergy are needed to optimize the role of MSMEs as an instrument to reduce poverty in rural areas